Latin American Heritage Interdisciplinary Dialogues on Brazilian and Argentinian Case Studies (The Latin American Studies Book Series,, 2018)
Focusing on Brazil, this book approaches the term "heritage" from not only a historical and architectural point of view, but also considers its artistic, archaeological, natural, ethnological and industrial aspects. The book is divided into four thematic sections - 1) traditions and intangible heritage, 2) archaeological heritage, 3) natural heritage and landscapes, and 4) heritage of industrial and built environments - and presents chapters on a diverse range of topics, from samba and cultural identities in Rio de Janeiro, to the history of Brazilian archaeology, the value of scenic landscapes in Brazil, and the cultural landscape of Brazil. As an outcome of the First Heritage International Symposium, this unique book explores a variety of heritage dialogues, pursuing global and specific approaches, and combining different views, perceptions and senses.